Registration of 'Linkert' Spring Wheat with Good Straw Strength and Adult Plant Resistance to the Ug99 Family of Stem Rust Races. Issue 2 (1st February 2018) - Anderson, J. A.; Wiersma, J. J.; Linkert, G. L.; Reynolds, S.K.; Kolmer, J. A.; Jin, Y.; Rouse, M.; Dill-Macky, R.; Hareland, G. A.; Ohm, J.-B.
Abstract : Straw strength is one of the most important criteria for spring wheat ( Triticum aestivum L.) cultivar selection in the north central United States. 'Linkert' (Reg. No. CV‐1137, PI 672164) hard red spring wheat was released by the University of Minnesota Agricultural Experiment Station in 2013 and has very good straw strength, high grain protein concentration, strong gluten, and good bread baking characteristics along with competitive grain yields. Linkert is moderately susceptible to Fusarium head blight, is moderately resistant to the prevalent races of leaf rust, and has field resistance to the Ug99 family of stem rust races, a rarity among spring wheat cultivars adapted to the region.